ANALISIS VEGETASI GULMA PADA PERLAKUAN OLAH TANAH TANAMAN UBI KAYU NUABOSI - Maria Tensiana Tima; Putri Titin Safarni; Sri Wahyuni (Agriculture Faculty of Flores University, 2022)
The growing weeds in cassava plants are unwanted because it negatively inhibits growth and reduces tuber production in cassava. This research aims to determine differences in the types and populations of weeds in the treated and fallow soil treatment. This study used the proportion sampling method by calculating the number of weed species found in cassava plantations, separating each weed found according to the plot, identifying the types of weeds obtained, and recording the data in a table of the number and density of weeds. This research shows that the population and types of weeds have different amounts between the treated land treated and the treated fallow land. The highest weed population was found at the treatment of fallow land with clover weed (Trifolium repens) of 1,462. In the tillage treatment, the highest weed population yield was found in the bandotan weed (Ageraum conyzoides) with a total population of 269. Based on observations, cassava plants on processed land had better development compared to cassava development on fallow land treatment.